PENERAPAN MEDIA (MONAS) “MONOPOLI NORMA DI MASYARAKAT” DALAM PEMBELAJARAN PENDIDIKAN PANCASILA UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS V SDN DUPAK 1 SURABAYA - Nur Lailis Sa’adah; Roni Rodiyana; Dwi Natalia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research was carried out with the aim of improving student learning outcomes by implementing the media (MONAS) "Monopoly on Norms in Society in the Pancasila education subject for class V elementary school. This research uses the type of classroom action research (PTK). This research was carried out in two cycles consisting of 2 meetings through 4 stages, namely planning, implementation, observation and reflection. The subjects in this research were students in class V of Elementary School at SDN Dupak 1 Surabaya, totaling 32 students. The data analysis technique used in this research is a qualitative descriptive data analysis technique. The results of student observations in cycle I reached 86%, then increased to 96% in cycle II. This percentage gain shows an increase of 10%. The percentage of classical learning completion for class V students at SDN Dupak 1 Surabaya in cycle I was 3.33%, and increased again in cycle II to 93%. This percentage shows an increase of 90% compared to the previous cycle. From these results it can be concluded that by implementing the media "MONAS" (Monopoly Norms in Society) can improve student learning outcomes in class V Norm material at SDN Dupak 1 Surabaya.